One dimensional edge localized YSR states in CrCl3 on NbSe2 - Jan P. Cuperus; Arnold H. Kole; Andrés R. Botello-Méndez; Zeila Zanolli; Daniel Vanmaekelbergh; Ingmar Swart (npj Quantum Materials)
Abstract Magnet/superconductor hybrid systems have been put forward as a platform for realizing topological superconductivity. We investigated the heterostructure of ferromagnetic monolayer CrCl3 and superconducting NbSe2. Using low-temperature scanning tunneling microscopy, we observe topologically trivial Yu-Shiba-Rusinov (YSR) states localized at the edge of CrCl3 islands. DFT simulations reveal that the Cr atoms at the edge have an enhanced d-orbital DOS close to E F . This leads to an exchange coupling between these atoms and the substrate that rationalizes the edge-localization of the YSR states.